Análise de atividades em livros didáticos de inglês - Costa, Daniela Gonçala da (2021)
This study attempted to demonstrate the centrality of activities in textbooks based on Chervel's concepts about school subjects. A quantitative analysis of the activities was carried out in two English textbooks for Elementary School approved by the National Textbook Program. The aim was to understand what kind of teaching the activities promote, what are the cognitive actions that are intended for students to develop based on Anderson and Krathwohl's taxonomy. It was also analyzed the teaching resources used in the activities and what type of learning the activities promote in order to achieve the purposes of English language learning for Elementary School according to the national curriculum. This study analyzed the 8th grade textbook of Alive! textbook approved in the 2014 and 2020 PNLD, considering the different curricula that guided the production of each edition, the PCN (1998) and the BNCC (2017), for the comparative analysis between the two textbooks. The fields of knowledge that are the basis for this study are school subject, textbook and curriculum. It was possible to observe that, in general, the knowledge that is expected to be developed in textbooks correspond to the factual and conceptual types, which are worked mainly by simple actions such as remembering and understanding. There was no strong relationship between teaching resources and activities. Regarding the curriculum, there is a link between both materialities when presenting activities that manifest the socio-interactional methodology of learning and language as a social practice, and the predominance of written comprehension activities and activities with more analytical or critical perspectives